Structures, microstructures, physical and chemical properties of different rice grains. (1st February 2019) - Xie, Ruishi; Li, Yuanli; Huang, Heyan; Guo, Baogang; Gao, Mei; Liu, Haifeng; Song, Mianxin; Zhang, Xingquan; Ma, Yongjun
Abstract: Herein, we demonstrated a well-rounded exploration of the universal structures, microstructures and physical properties of different rice grains. We show that these rice grains are nanocrystalline in nature, have the standard pattern of type A rice crystalline, and can be attributed to the hexagonal crystal structure with space group of P 6. These rice grains have uneven surfaces, clusters of the granules, or schistose structure. Carbon, nitrogen and oxygen elements are presented in the rice grains. No significant difference is observed in FTIR spectra in these rice grains, indicating the fundamental chemical structures of these rice grains are analogical. Their microstructural and physical properties were investigated in detail. Moreover, chemical properties (e.g. thermal stability) of the rice grains were explored. This research provides an in-depth understanding on the physical and structural properties on the atomic and molecular level, as well as guidance for food and industry applications.